2013
DOI: 10.1002/acr.22143
|View full text |Cite
|
Sign up to set email alerts
|

Variations Among Primary Care Physicians in Exercise Advice, Imaging, and Analgesics for Musculoskeletal Pain: Results From a Factorial Experiment

Abstract: Objective To examine whether medical decisions regarding evaluation and management of musculoskeletal pain conditions varied systematically by characteristics of the patient or provider. Methods We conducted a balanced factorial experiment among primary care physicians in the U.S. Physicians (N=192) viewed two videos of different patients (actors) presenting with pain: (1) undiagnosed sciatica symptoms or (2) diagnosed knee osteoarthritis. Systematic variations in patient gender, socioeconomic status (SES), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
0
29
1
Order By: Relevance
“…Furthermore, because higher perceived benefits of exercise were associated with the timing of response, we speculate that clinicians can improve the effectiveness of exercise among older adults through frequent encouragement, specific guidance, and regular use of exercise prescriptions. Although clinician recommendation is the single most important determinant for exercise engagement in OA [61], less than one‐third of physicians in the United States provide any exercise advice for these patients [62]. Thus, physicians may play an important role in improving exercise outcomes in knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because higher perceived benefits of exercise were associated with the timing of response, we speculate that clinicians can improve the effectiveness of exercise among older adults through frequent encouragement, specific guidance, and regular use of exercise prescriptions. Although clinician recommendation is the single most important determinant for exercise engagement in OA [61], less than one‐third of physicians in the United States provide any exercise advice for these patients [62]. Thus, physicians may play an important role in improving exercise outcomes in knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the transmission of evidence-based messages regarding selfmanagement, most barriers reside at the level of the health care provider. Despite current evidence-based recommendations, less than one-third of primary care providers deliver advice about exercise and/or lifestyle changes for patients with osteoarthritis (26). In addition, a 2011 survey of adults in the US suggested there is a low occurrence of shared decision-making in the clinical setting (27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining physician experience and test ordering have shown higher cost profiles in physicians with less experience [27,34,35]. Variable data is available on the relationship between physician gender and practice patterns, with some showing no consistent effect on test ordering [36], and others demonstrating significantly higher ordering rates by female physicians [27,37]. With regard to adherence to clinical guidelines, Ferrier et al showed female and younger physicians were more likely to use practice guidelines than their male and older counterparts [38].…”
Section: Non-thrombotic Clinically Significant Findingsmentioning
confidence: 97%